Effect of negotiation skills training program on head nurses’ knowledge and behavior - Hanaa M. Moustafa; Rabab M. Hassan; Fawzia M. Badran (BMC Nursing)
Abstract Background Negotiating is a common occurrence and a significant part of everyday tasks for head nurses. The ability of the head nurse to effectively negotiate is a crucial management tool for work management in healthcare facilities. Aim The present study aimed to assess the effect of negotiation skills training program on head nurses’ knowledge and behavior. Methods A pretest–posttest, one-group quasi-experimental design was conducted at Menoufia University Hospitals. It is located in Shebeen, Elkom City, Cairo, Egypt. All head nurses and their assistants and their number 64 head nurses. Results The results indicated that a minority of head nurses had satisfactory knowledge regarding negotiation in the pretest phase and obviously increased in the posttest to be more than three quarters and slightly decreased in the follow-up phase. Also, a minority had a high negotiation behavior level in the pretest phase and increased to be more than half in the posttest with a slight decrease in the follow-up stage. There was a highly statistically significant difference between pre-, post-, and follow-up results regarding negotiation knowledge and behavior. Conclusion The study revealed that the head nurse’s knowledge and behavior increased markedly after implementing the negotiation skills training program. Recommendations Conduct continuous education and training programs for stimulating and developing head nurses’ knowledge, behavior regarding negotiation, and hospital administration should support the importance of negotiation skills to both head nurses and organizations. Trial Registration Number [TRN] The study protocol was approved by the Research Ethics Committee of the Faculty of Nursing, Ain Shams University (code number: NUR 23.10.131).